Análise da paternidade de Caiman crocodilus crocodilus (L.) da reseva de desenvolvimento sustentável Piagaçu-Purus, utilizando marcadores microssatélites - Oliveira, Deyla Paula de (Instituto Nacional de Pesquisa da Amazônia - INPA, 2010)
Recently genetic studies have been utilized to study breeding systems of several crocodilian, however, no paternity studies involved Caiman crocodilus crocodilus. To investigate paternity, it is necessary to use highly polymorphic microsatellite loci that have high probability of exclusion of paternity and differentiating individuals. For this purpose 12 dinucleotide microsatellite loci were isolated and characterized from a genomic library enriched for the dinucleotide repetitions (CT) 8 and (GT) 8 . The 12 loci were characterized in C. c. crocodilus from the Piagaçu-Purus Sustainable Development Reserve, Amazonas, and their utility also tested in Caiman c. yacare from Cacéres, Mato Grosso. The results of the characterization indicated that these loci are adequate for the study of the breeding system and also for population studies with the Caiman crocodilus complex. Six loci with highest polymorphism, high power of paternity exclusion and with high probability of differentiating among individuals were used in a PCR multiplex system for breeding system analysis of the C. c crocodilus from the Piagaçu-Purus Sustainable Development Reserve. We genotyped 198 hatchlings from 13 nests (representing a sampling effort that varied from 30% to 100% of the hatchlings per nest) sampled in the two reproductive seasons (2007 and 2008), as well as 11 females that were beside their respective nests and 21 males, potential fathers. In 100% of the nests there was a contribution of two to four fathers, all males contributed approximately equally per clutch, and none of the genotyped males were the actual fathers of the hatchlings. No male mated with more than one female, and no female showed across-year male fidelity. All females found in proximity of nests were mothers of the hatchlings of those nests. Our study highlights that polyandry is common in this species, that no single male reproductively dominates, and that females mate with geographically distant males. Our results have important implications for conservation efforts and species management in the study area and beyond.
Keywords: Jacarétinga; Marcadores genéticos; Testes de paternidade